2012
DOI: 10.1007/s11356-012-1105-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of selected essential (Co, Cu, Fe, Mn, Mo, Se, and Zn) and nonessential (Cd, Pb) trace elements among protein fractions from hepatic cytosol of European chub (Squalius cephalus L.)

Abstract: Association of selected essential (Co, Cu, Fe, Mn, Mo, Se, and Zn) and nonessential (Cd, Pb) trace elements with cytosolic proteins of different molecular masses was described for the liver of European chub (Squalius cephalus) from weakly contaminated Sutla River in Croatia. The principal aim was to establish basic trace element distributions among protein fractions characteristic for the fish living in the conditions of low metal exposure in the water. The fractionation of chub hepatic cytosols was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
39
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 52 publications
20
39
4
Order By: Relevance
“…In 1991, Klaverkamp et al [12] reported that in white suckers collected from a metal-contaminated environment, half of the hepatic Cu burden was bound to MT. Our results showed that Cu distribution in white suckers agreed with previous studies investigating Cu-binding biomolecules in the liver of freshwater fish collected in metal-impacted areas, where most of Cu was present at the same elution time as the elution time for MT (European eels (Anguilla anguilla) [13,14]; European chub and Vardar chub (Squalius cephalus and S. vardarensis) [15,16]; gibel carp (Carassius auratus gibelio) [17]). Comparable interpretations were made in field-collected juvenile yellow perch (Perca flavescens), although the major Cu peak did not elute at exactly the same elution time as was observed for the MT standard [18]; many isoforms of MTs co-exist and may explain this difference [17].…”
Section: Copper (Cu)supporting
confidence: 90%
See 1 more Smart Citation
“…In 1991, Klaverkamp et al [12] reported that in white suckers collected from a metal-contaminated environment, half of the hepatic Cu burden was bound to MT. Our results showed that Cu distribution in white suckers agreed with previous studies investigating Cu-binding biomolecules in the liver of freshwater fish collected in metal-impacted areas, where most of Cu was present at the same elution time as the elution time for MT (European eels (Anguilla anguilla) [13,14]; European chub and Vardar chub (Squalius cephalus and S. vardarensis) [15,16]; gibel carp (Carassius auratus gibelio) [17]). Comparable interpretations were made in field-collected juvenile yellow perch (Perca flavescens), although the major Cu peak did not elute at exactly the same elution time as was observed for the MT standard [18]; many isoforms of MTs co-exist and may explain this difference [17].…”
Section: Copper (Cu)supporting
confidence: 90%
“…Co-elution with Cu was also reported, and the authors speculated that the metal-binding ligand was probably MT. Cadmium presence in the cytosol and its probable binding to MT were previously reported for the liver and gills of Vardar and European chubs collected in metal mining-impacted rivers [15,16,19]. Increased Cd associated with hepatic MT was also reported in field-collected European eels (Anguilla anguilla) and gibel carp (Carassius auratus gibelio) [14,17].…”
Section: Cadmium (Cd)supporting
confidence: 52%
“…Our results are in accordance with the demonstration made by Bury and Grosell (2003) that Fe can be absorbed from the water by the gills in teleost fish. In addition, among essential elements, Fe is well known for its tendency to accumulate in living organisms in a form of ferritin, especially in fish liver (Krasnići et al 2013). Unlike Fe, which was observed to accumulate in different chub organs , the most of the essential elements are kept within narrow boundaries in fish organism, and only the conditions of high metal exposure, much higher compared to naturally found water metal concentrations, would result in metal bioaccumulation in fish organs.…”
Section: Association With the Level Of Exposurementioning
confidence: 99%
“…Caron et al (2018) applied similar methodology to perform somewhat more extensive study on liver of juvenile yellow perch (Perca flavescens) regarding binding of several trace elements (Ag, Cd, Co, Cu, Ni, and Tl) to various cytosolic biomolecules. Our previous studies in this field included comprehensive investigation of cytosolic distributions of Cd, Co, Cu, Fe, Mn, Mo, Pb, Se, and Zn in the liver and gills of European chub (Squalius cephalus) from the moderately contaminated Sutla River in Croatia (Krasnići et al, 2013(Krasnići et al, , 2014 and of Vardar chub (Squalius vardarensis) from highly contaminated Macedonian rivers .…”
Section: Introductionmentioning
confidence: 99%
“…/j.chemosphere.2018 5 and to define the distribution profiles among cytosolic biomolecules of different molecular masses for nine selected elements, two highly toxic metals (Cd and Tl) and seven essential elements (Co, Cu, Fe, Mn, Mo, Se, and Zn). As it is very likely that various fish species have different metal handling strategies, the additional aim of this study was to compare metal distribution profiles characteristic for brown trout liver with previously published profiles for liver of European chub (Krasnići et al, 2013) and…”
Section: Introductionmentioning
confidence: 99%